Banditry and Insecurity: Are There Ungoverned Spaces in Nigeria? - Kugbayi, Oluwaseun; Adegbami, Adeleke (Faculty of Law, Universitas Negeri Semarang, 2023)
Many towns and villages in Nigeria have been experiencing bandits activities, vis-à-vis kidnapping, armed robbery, murder, rape, cattle-rustling, and violent actions in recent years. These activities have continued to escalate despite the presence of security agencies such as – the Nigerian Army, the Nigerian Navy, the Nigerian Air Force, the Nigerian Police, the State Security Service, the National Intelligence Agency, and the Defence Intelligence among others. The unabated bandits' activities in part of the country depict a picture of ungoverned spaces, which suggests that there are territories that are experiencing a vacuum of political order. The study for that reason examines the connections between banditry and the ungoverned spaces, as well as, analyses the effects of bandits' activities on Nigeria and Nigerians. Using the discourse analysis that relies on secondary sources, the paper argues that the inability to govern some territories adequately in Nigeria has created a vacuum for bandits’ activities to thrive.